1993
DOI: 10.3354/meps101023
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of dissolved organic carbon by marine bacteria and demand for inorganic nutrients

Abstract: Seawater cultures were used to study seasonal and diel variations in bacterial growth and nutrient availability. In both the Baltic Sea and the Northeast Mediterranean, the least available component for bacterial growth was phosphorus. In the Baltic Sea, carbon was available in excess for bacterial growth on all sampling occasions. Compared to the controls, additions of nonlimiting concentrations of inorganic nitrogen and phosphorus increased the yield of bacteria compared to the control with 156% and the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

35
225
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(263 citation statements)
references
References 22 publications
35
225
3
Order By: Relevance
“…Shiah et al (1998) showed that DOC turn-over rate in the western equatorial Pacific could be enhanced two-to ninefold when inorganic nutrients were added. Similar findings were also reported in the Baltic and the Mediterranean seas (Zweifel et al, 1993), the North Atlantic (Kirchman et al, 1991), the Gulf of Mexico (Pomeroy et al, 1995) and even in estuarine ecosystems (Shiah and Ducklow, 1995).…”
Section: Discussionsupporting
confidence: 73%
“…Shiah et al (1998) showed that DOC turn-over rate in the western equatorial Pacific could be enhanced two-to ninefold when inorganic nutrients were added. Similar findings were also reported in the Baltic and the Mediterranean seas (Zweifel et al, 1993), the North Atlantic (Kirchman et al, 1991), the Gulf of Mexico (Pomeroy et al, 1995) and even in estuarine ecosystems (Shiah and Ducklow, 1995).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, despite the expected heterogeneity of the species composition of the bacterioplankton in the subtropical Atlantic (Giovannoni et al 1990, Mullins et al 1995, there is a clear diel pattern in bacterial cell division detectable, indicating phasing of growth. Such diel growth patterns have been reported previously for a number of coastal and open ocean regions and lentic systems , Riemann & Søndergaard 1984, Fuhrman et al 1985, Herndl & Malacic 1987, Zweifel et al 1993, Simon 1994, Gasol et al 1998. Most of these studies used the incorporation of radiolabeled thymidine and/or leucine to determine the diel growth pattern.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, phosphorus covaried strongly with community composition. It has previously been shown that the availability of phosphorus may limit bacterioplankton growth in the open oceans (for example, see (Cotner et al, 1997)) and in the Northern Baltic Sea (Zweifel et al, 1993), and select for specific bacteria adapted to such nutrient-deprived conditions (Pinhassi and Hagströ m, 2000). Hence, conceivably, the pronounced seasonal oscillations in phosphorus concentration observed at the sampling station, with potentially limiting conditions associated with the Cyanobacterial summer blooms (Table 1), exert a strong selection pressure onto the bacterial community.…”
Section: Discussionmentioning
confidence: 99%